1991
DOI: 10.1093/jnci/83.16.1164
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Weekly Intravenous Infusions of CPT-11, a New Derivative of Camptothecin, in the Treatment of Advanced Non-Small-Cell Lung Cancer

Abstract: 7-Ethyl-10-[4-(1-piperidino)-1-piperidino]carbonyloxy-camptothecin (CPT-11) is a novel camptothecin derivative that has been selected for clinical evaluation because of its broad spectrum of antitumor activity in animal models and its unique inhibitory effects on mammalian DNA topoisomerase I. Seventeen patients with advanced non-small-cell lung cancer were treated with CPT-11 at weekly dose levels ranging from 50 to 150 mg/m2. At least three weekly doses were given to all patients except four, and a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(93 citation statements)
references
References 0 publications
3
88
2
Order By: Relevance
“…The phase I clinical trial of CPT-11, in which CPT-11 was administered weekly, showed that the dose-limiting adverse effects were leucopenia and diarrhoea, and the recommended dose for the phase II monotherapy trial was 100 mg m À2 week À1 (Negoro et al, 1991). In the phase II clinical trial of CPT-11 monotherapy for patients with untreated advanced NSCLC, the response rate was 31.9% (23 out of 72 cases) and the MST was 42 weeks (Fukuoka et al, 1992).…”
mentioning
confidence: 99%
“…The phase I clinical trial of CPT-11, in which CPT-11 was administered weekly, showed that the dose-limiting adverse effects were leucopenia and diarrhoea, and the recommended dose for the phase II monotherapy trial was 100 mg m À2 week À1 (Negoro et al, 1991). In the phase II clinical trial of CPT-11 monotherapy for patients with untreated advanced NSCLC, the response rate was 31.9% (23 out of 72 cases) and the MST was 42 weeks (Fukuoka et al, 1992).…”
mentioning
confidence: 99%
“…Modified FOLFIRI regimen was used every14 days, the others were every 21days. Because toxicity of irinotecan results in leukopenia and diarrhea is dose-limiting (Negoro et al, 1991), once patients occurred grade IV toxicity, the dosage would be adjusted next chemotherapy. No restriction was put on whatever the previous chemotherapy regimens course CPT-11 in patients according to their basic clinic characters and their UGT1A1 genotypes.…”
Section: Patientsmentioning
confidence: 99%
“…Because CPT-11 causes severe diarrhea and neutropenia in 20% to 35% of patients treated (Negoro et al, 1991;Rothenberg, et al, 1993;Rougier et al, 1998;Saltz et al, 2000;Rothenberg et al, 2001;Vanhoefer et al, 2001;Fuchs et al, 2003), and fatal events (up to 5.3% prevalence) during single-agent irinotecan treatment have been reported (Vanhoefer et al, 2001). We associated these two kind side effects with UGT1A1 genotypes, clinic characters and each other to detect the relationship between them by multivariate logistic analysis We took the sex, age, KPS, number of metastasis, history of chemotherapy, UGT1A1 genotype, dosage, leucopenia, neutropenia, primary cancer and pathological type into risk factors.…”
Section: Figure 2 Serum Total Bilirubin Distribution Of Different Gementioning
confidence: 99%
See 2 more Smart Citations